2011
DOI: 10.1118/1.3554644
|View full text |Cite
|
Sign up to set email alerts
|

Study of the response of plastic scintillation detectors in small‐field 6 MV photon beams by Monte Carlo simulations

Abstract: Purpose:To investigate the response of plastic scintillation detectors ͑PSDs͒ in a 6 MV photon beam of various field sizes using Monte Carlo simulations. Methods: Three PSDs were simulated: A BC-400 and a BCF-12, each attached to a plastic-core optical fiber, and a BC-400 attached to an air-core optical fiber. PSD response was calculated as the detector dose per unit water dose for field sizes ranging from 10ϫ 10 down to 0.5ϫ 0.5 cm 2 for both perpendicular and parallel orientations of the detectors to an inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 25 publications
(21 reference statements)
3
37
0
Order By: Relevance
“…If only large fields are considered, the PSD can be compared to the SD, the IC and Gafchromics, all four detectors are within a 1.3% margin for the 35 mm cone. Finally, the response of PSD has been evaluated with Monte Carlo by Wang and Beddar 24 and has shown variations within 0.4% for field sizes ranging from 0.5 Â 0.5 cm 2 to 10 Â 10 cm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…If only large fields are considered, the PSD can be compared to the SD, the IC and Gafchromics, all four detectors are within a 1.3% margin for the 35 mm cone. Finally, the response of PSD has been evaluated with Monte Carlo by Wang and Beddar 24 and has shown variations within 0.4% for field sizes ranging from 0.5 Â 0.5 cm 2 to 10 Â 10 cm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to diode detectors, PSD are energy independent and hence no daisy chain method was necessary. However, PSD are susceptible to over responding when exposed to radiation due to Cherenkov light generated in the optic fiber . To overcome this issue, a SuperMAX electrometer (Standard Imaging) was used for online Cherenkov radiation correction.…”
Section: Methodsmentioning
confidence: 99%
“…There are many publications on the dosimetric characteristics of the PSD . Among which, several studies demonstrated that the PSD achieved similar dose response to other widely accepted benchmarks, such as Monte Carlo, Gafchromic films and diamond detectors .…”
Section: Introductionmentioning
confidence: 99%